The Study of Systemic Functional Linguistic (SFL) on EFL Students’ Writing in Making Caption - Laela Nurfadilah; Yogi Setia Samsi; Abdul Kodir Al-Baekani (Jurnal Ilmiah Wahana Pendidikan, 2022)
Students in Indonesian high schools reviewed a great deal of material. They need to have a firm understanding on a variety of texts. Caption text is one of the texts that the students need to be able to understand fluently. The students are still having trouble writing a caption text. In order to make this research more focused, the researcher narrowed the field of the problem being studied to investigate EFL students' writing in the process of making captions based on SFL perspectives. This research used a case qualitative method. The result showed that students worked hard to create a caption text. They found two important things about the structure and language of the genre as a whole. They have exercised good control in writing caption text in terms of generic structure. The schematic structure of the caption texts demonstrates this. There are still several spelling, punctuation, and capitalization errors in the language. Learning to write cannot be accomplished in a single session. Thus, in order to successfully create a meaningful writing class, both teachers and students must maintain active communication.